Image-Based Virtual Navigation System for Art Caves - Lu, Dongming; Pan, Yunhe (International Journal of Virtual Reality, 2000)
Dunhuang Art Cave (DAC), one of the most famous cultural heritage sites in the world, is confronted with serious natural efflorescence. How to virtually rebuild the caves and support their investigation and exploitation with computer graphics (CG) and Virtual Reality (VR) technologies is an urgent and important project. In this paper we discuss in detail the essential technical issues in our image-based virtual DAC navigation system. For DAC modeling of the cave architecture we employ 3D surface modeling, texture and 2D image-based modeling, murals, and painted statues. For DAC rendering we use the level of detail (LOD) method for murals and image-based rendering for painted statues. For DAC shadow generation we investigate a simple 3D model-based solution. Finally, this paper will show the general system architecture as well as demos of virtual navigation.